Potential Use of a Salt Gradient Solar Pond to Store Thermal Energy - Daniel Vinícius Silva Veras; Rafael da Costa Ilhéu Fontan; Lizzy Ayra Alcantara Veríssimo; Ana Paula Fonseca Machado; Cecília Alves Mourão; Renata Cristina Ferreira Bonomo (Semina: Ciências Exatas e Tecnológicas, 2012)
Demand for energy sources that allow a sustainable development has stimulated studies on the acquisition of alternative energy, renewable and clean such as hydro, wind, biomass and solar energies. Therefore, the objective in this work was to evaluate the potential of a Salt Gradient Solar Pond (SGSP) in order to obtain thermal energy from solar energy. A pilot solar pond with 1,76 m² of surface area and 1 m³ of volume was set up in Itapetinga, Bahia, and temperatures in upper and lower convective layers were monitored between August 20 and November 3, 2008. It was found that the temperature difference between the layers increased from 2°C to 13.2°C, with a medium value of 5.7°C for the period. Considering a 30% efficiency for utilization of stored energy, it would be possible increase by 10°C the temperature of 50 L of chilled milk in a dairy industry, thus demonstrating its potential. In the end of Spring or Summer the temperature difference would be superior. Results demonstrate the potential use of solar ponds by industries and farms in our country, as a renewable and non-polluting alternative, being able to store thermal energy from solar energy.